LEVEL OF PHYSICAL ACTIVITY AND LIPID CONSUMPTION PROFILE IN SELECTED SUBJECTS IN THE VALE DO SINOS REGION, RS, BRAZIL. (Fiep Bulletin - online, 2014)
It is well-estabilished that physical inactivity and low fitness level have been considered risk factors for early mortality which are as important as smoking, dyslipidemias and hypertension. Similarly, the excessive consumption of fat also contributes for the increase of obesity and cardiovascular disease risk. The aim of this study was to describe lipid consumption related to the level of physical activity (PA) of adults in Vale do Sinos, RS. For this study, 597 subjects from 18 to 81 years old were selected according to the residence criterion of Instituto Brasileiro de Geografia e Estatística - IBGE, living in towns in Vale do Sinos, RS. BMI was calculated through height and body mass. The level of PA was assessed through the application of the International Physical Activity Questionnaire (IPAQ), short version. Lipid consumption was calculated through 24h food record. ANOVA, from the statistical package SPSS 12.0, was used in order to test differences between PA levels, considering p
Keywords: physical activity; BMI; lipids